Crafting customer experience strategy : lessons from Asia - Popli, Sapna; Rishi, Bikramjit (Emerald Publishing Limited, 2021)
When analysing customer experience, there is often a disconnect in the kind of customer experience senior leadership believes their organizations deliver and what consumers say they actually receive. Crafting Customer Experience Strategy: Lessons from Asia looks at how Customer Experience Management can be vital in providing a sustained competitive advantage for businesses. In uncovering this essential strategic challenge, this book explores the need to create customer experiences by design utilizing data, as well as the importance of engaging with the voice of the customer, the employee and the process in managing the customer journey. In this book a range of real world insights are scrutinized from a variety of leading organizations; chapters explore a wide range of themes including how organizations create experiences, the customer journey, emotions, technology and the returns in designing improved experiences. This is an essential reading for marketing students, scholars and practitioners looking for understanding and insights in customer experience management.